2023
DOI: 10.3390/nano13101614
|View full text |Cite
|
Sign up to set email alerts
|

3D Hierarchically Structured Tin Oxide and Iron Oxide-Embedded Carbon Nanofiber with Outermost Polypyrrole Layer for High-Performance Asymmetric Supercapacitor

Abstract: Herein, unique three-dimensional (3D) hierarchically structured carbon nanofiber (CNF)/metal oxide/conducting polymer composite materials were successfully synthesized by combinations of various experimental methods. Firstly, base CNFs were synthesized by carbonization of electrospun PAN/PVP fibers to attain electric double-layer capacitor (EDLC) characteristics. To further enhance the capacitance, tin oxide (SnO2) and iron oxide (Fe2O3) were coated onto the CNFs via facile hydrothermal treatment. Finally, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 111 publications
0
1
0
Order By: Relevance
“…Each curve includes a semicircle in the highfrequency region and a linear par in the low-frequency region, with the diameter of the semicircle representing the charge transport resistance (R ct ) and the slope of the straight line standing for the diffusion resistance (R w ). [49,55] It can be observed that all samples have almost overlapping semicircles in the high-frequency region, indicating that they have close R ct and equivalent series resistance (R s ) which can be obtained by the intersection of the curve with the Z' axis and mainly determined by the electrolyte. [56] In the low-frequency region, the linear slope decreases with the increase of selenide, indicating that the introduction of metal selenide will reduce the specific surface area of the material, limiting the diffusion of electrolyte ions in the composites.…”
Section: Resultsmentioning
confidence: 99%
“…Each curve includes a semicircle in the highfrequency region and a linear par in the low-frequency region, with the diameter of the semicircle representing the charge transport resistance (R ct ) and the slope of the straight line standing for the diffusion resistance (R w ). [49,55] It can be observed that all samples have almost overlapping semicircles in the high-frequency region, indicating that they have close R ct and equivalent series resistance (R s ) which can be obtained by the intersection of the curve with the Z' axis and mainly determined by the electrolyte. [56] In the low-frequency region, the linear slope decreases with the increase of selenide, indicating that the introduction of metal selenide will reduce the specific surface area of the material, limiting the diffusion of electrolyte ions in the composites.…”
Section: Resultsmentioning
confidence: 99%
“…The specific capacitances measured from the GCD curves were 18.7, 20.4, 24.0, 27.5, 33.6, and 40.8 F g −1 in the operating voltage windows of 1.0, 1.2, 1.4, 1.6, 1.8, and 2.0 V, respectively. The specific capacitance increases with the broadening of the operating voltage window owing to the pseudocapacitive reaction [24]. Moreover, the coulombic efficiencies were calculated as 89.3, 87.1, 88.2, 86.9, 88.6, and 87.5%, respectively, indicating the reversible properties of the ASC device, even at a high voltage of 2.0 V. Figure 6b presents the GCD curves of the ASC device at different current densities within the 2.0 V voltage window.…”
Section: Electrochemical Performance Of the Assembled Asc Devicementioning
confidence: 99%
“…However, the limitations for pseudo-type materials include poor cycling stability and low electrical conductivity [23]. To overcome the limitations of these two types, hybrid-type materials are synthesized by incorporating metal oxides and conducting polymers into carbonaceous materials [24]. Due to the synergistic effect, hybrid-type materials exhibit various positive characteristics in regards to energy/power density and cyclability [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation